(untitled) (Journal of the Bangladesh Agricultural University, 2010)
Chickpea (Cicer arietinim) husk was extracted by non-alkaline aqueous extraction process. The residual extracted husk was dried in a cabinet drier and finally ground. Both fresh husk and processed husk were analyzed for their composition. The processed husk (extracted ground husk) was incorporated into formulations of cracker biscuits at 0- 20% replacement levels of wheat flour and baking functionalities were evaluated. The studies on the effects of processed husk on biscuit’s qualities showed that the highest spread ratio of biscuits was achieved with 3% processed husk. Analysis of cracker biscuits containing various percentage of processed husk showed that biscuits with increasing level of processed husk had higher ash, fat, moisture and crude fiber content, while lower protein and total carbohydrate content. The amount of crude fiber content of biscuits significantly increased with the incorporation of processed husk when compared with conventional biscuits. The cracker biscuits containing various percentages of processed husks were evaluated for their sensory attributes. The results revealed that cracker biscuits containing 5% processed husk secured the highest score for overall acceptability among other substitution levels. Keywords: Chickpea husk; Cracker biscuits; Crude fiber; Baking properties DOI: 10.3329/jbau.v8i1.6412 J. Bangladesh Agril. Univ. 8(1): 147-152, 2010